Assessment of Foetal DNA in Maternal Blood – A Useful Tool in the Hands of Prenatal Specialists - Kagan, K. O.; Hoopmann, M.; Kozlowski, P. (Geburtshilfe und Frauenheilkunde, 2012)
Over the last few years, first trimester screening between 11+ and 13+ weeks of gestation has become one of the most important ultrasound examinations in pregnancy, as it allows physicians to predict several pregnancy complications including pre-eclampsia or pre-term birth. Screening for trisomies 21/18 and 13 using maternal and gestational age, foetal nuchal translucency, and maternal serum biochemistry was formerly the main reason for first trimester screening. However, today this is only one part of the overall examination. In the near future, the analysis of foetal DNA obtained from maternal blood will be used to supplement first trimester screening for aneuploidy or even replace current screening methods. In this review we show how prenatal medicine specialists can use foetal DNA analysis.
Keywords: foetal DNA; ultrasound; first trimester screening; trisomy